USERS’ RATING ON THE IMPROVED LIBRARY ORIENTATION PROGRAMME AT ZARQA PRIVATE UNIVERSITY: A COMPARATIVE STUDY - Fadel, Jamil Klaib (Malaysian Journal of Library and Information Science, 2017)
Findings of a study on library orientation programme conducted in 2008 at Zarqa Private University Jordan revealed that the offered programme had focused more on theoretical rather than the practical aspects. Subsequently, another study was conducted whereby an improved programme was offered to first year students in the second semester of the academic year 2008/2009. The programme covers three courses which concentrated on (a) practical library skills, (b) writing research requirements and (c) formulating research methodology. This study makes comparisons between the students’ ratings on their perceived achievement of the programme objectives in both studies. Data were collected from 155 usable questionnaires returned by the population of 621 first year students (25% response rate). Study findings indicate that (a) the average of mean of students’ ratings on the achievement of the practical objectives of the improved library orientation programs is higher (3.28) than the mean found in the previous study (2.91); and (b) in spite of the improvement of respondent’s ratings in the current study, there is still a need, in the future, to offer long time library orientation programmes that concentrate on more practical aspects.